Pembuatan Filter Air Sederhana Sebagai Upaya Penyediaan Air Bersih Di Desa Sedulang - Oktawati, Nurul; Rafii, Rahmat; Rohmah, Faisatur; Azzahra, Aulia; Sekar, Roro; Arif, Mutiara Salsabillah; Purba, Anggun Trianita Kencana; Wulanatta, Wahyuni; Amelia, Della; Paraswati, Dila Ayu; Ridho, Aisyatur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
Sedulang Village is known for its rich natural resources, but the biggest challenge faced by the community is the water quality that is not fully adequate. Therefore, this community service program aims to provide solutions in the provision of clean water by making simple water filters that are easily applied by the community. The methods used in this program include field observations, experiments in making water filters, and evaluation of the effectiveness of water filtration before and after filtration. Results show that this simple filtration system is able to reduce water turbidity by 70% and eliminate odors caused by organic content. The active participation of the community in the process of making and maintaining the filter contributes to the sustainability of this program.